2015
DOI: 10.2169/internalmedicine.54.3313
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Causes of Fever of Unknown Origin and Inflammatory Markers: A Multicenter Collaborative Retrospective Study

Abstract: The present study identified inflammatory markers that should be considered in the differential diagnosis of classical FUO, providing useful information for future diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
(33 reference statements)
2
17
2
Order By: Relevance
“…The finding was not in line with the previous study by Naito et al (31), probably due to the limited number of subjects in the previous study. PCT levels were measured in only 45 patients with FUO.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The finding was not in line with the previous study by Naito et al (31), probably due to the limited number of subjects in the previous study. PCT levels were measured in only 45 patients with FUO.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in line with previous studies (27,31). Although these 3 indices would be elevated in inflammatory conditions, they are nonspecific for the differential diagnosis of FUO.…”
Section: Discussionsupporting
confidence: 93%
“…Naito et al concluded that a normal erythrocyte sedimentation rate (ESR) could exclude the presence of a malignancy (1). Based on the contents of their manuscript, we have two questions: First, did the authors consider any other influencing factors in the elevation of the ESR?…”
mentioning
confidence: 99%
“…Naito et al reported a nationwide retrospective study that included a large cohort of patients with FUO who had visited the general medicine department at one of 17 affiliated hospitals in Japan (6). The authors examined the relationships between underlying diseases and levels of inflammatory tests, WBC, ESR, CRP, and procalcitonin.…”
mentioning
confidence: 99%
“…The study was conducted at 17 hospitals affiliated with the Japanese Society of Hospital General Medicine (6). General internal medicine (GIM) is at the intersection of other medical subspecialties, and covers almost all adult medical issues.…”
mentioning
confidence: 99%